"USE OF COLORS IN GRAPHICS ARTS IN INDIA": “भारत में ग्राफिक्स कला में रंगों का उपयोग” - Gautam, Reena (International Journal of Research -GRANTHAALAYAH, 2014)
A large number of printings were produced in India and many artists including William and Daniel explored the possibilities of art in India and both artists produced original amalgamated color prints called ’Twelve Views of Calcutta’ between 1786-88 The paintings were printed in one color and colored with colored ink. ; 9 After this activity of printing, colorful printings were produced in many places in the country, in which Calcutta was the center. In this way, the production of colorful advertising prints also started. भारत में अत्यधिक मात्रा में छापाचित्रों का निर्माण किया गया और अनेकों कलाकारों जिनमें विलियम और डेनियल ने छापा कला की भारत में संभावनाओं को टटोला और दोनों कलाकारों ने 1786-88 के मध्य ‘ कलकत्ता के बारह दृश्य’ नामक मूल अम्लांकन रंगीन छापाचित्रों का निर्माण किया जिनमें चित्रों को एक रंग में छापा गया और उनको रंगीन स्याही से रंगदार बनाया गया। ;9द्ध छापाकला की इस गतिविधि के बाद देश में अनेकों जगह रंगीन छापाचित्रों का निर्माण किया जाने लगा जिनमें कलकत्ता केंद्र था । इस प्रकार रंगीन विज्ञापन छापाचित्रों का भी निर्माण भी शुरू हो गया ।